Cognitive behavioural therapy plus Kiesler Circle Training (CBT+) versus CBT only for patients with interpersonal problems: study protocol for a randomised controlled feasibility trial - Stephan Köhler; Philipp Sterzer; Eva-Lotta Brakemeier; Karen Ollrogge; Daniel Schulze; Eva Friedel; Nina Romanczuk-Seiferth; Anna-Lena Siegerist; Anne Guhn (BMJ Open)
Introduction Interpersonal problems are a transdiagnostic risk factor for the development and maintenance of various psychiatric disorders, including anxiety and depression. Interventions that address these interpersonal challenges could therefore play a crucial role in enhancing mental health. This study aims to evaluate the efficacy and feasibility of a transdiagnostic group intervention, the Kiesler Circle Training (KCT), in improving interpersonal skills.Methods and analysis In a prospective randomised controlled trial (RCT), 156 outpatients with a primary diagnosis of either depression or anxiety disorder according to DSM-5, and significant interpersonal problems, will be investigated. All patients will receive individual, state-of-the-art cognitive behavioural therapy (CBT) during the study. They will be randomly assigned to one of two conditions: the experimental group will receive the KCT in group sessions, in addition to individual CBT, while the control group will receive only individual CBT. The KCT intervention consists of 1 introductory individual session and 12 weekly group sessions, each lasting 100 min, with groups of up to 10 patients. KCT includes five sequential modules: the interpersonal circle, nonverbal communication, verbal communication, conflict resolution and empathy training. It is hypothesised that the experimental group will show (a) greater reduction in interpersonal problems from pre-assessment to post-assessment and (b) greater symptomatic improvement regarding the primary diagnosis. Child maltreatment is expected to moderate the trajectory of interpersonal problems. This study aims to provide evidence for the feasibility of KCT as a modular transdiagnostic add-on approach for patients with interpersonal difficulties.Ethics and dissemination This study obtained approval from the ethics committees at the Charité Berlin, the Medical School of Berlin and the University of Greifswald. All results will be disseminated through peer-reviewed articles in scientific journals and contributions to national and international conferences.Trial registration number DRKS00032467, NCT06170801 (see Supplementary Material).